1985
DOI: 10.1007/bf02554049
|View full text |Cite
|
Sign up to set email alerts
|

Cocaine colitis

Abstract: An unusual case of colitis in a 37-year-old cocaine addict is described. The patient presented with right-sided abdominal pain and diarrhea exacerbated by his use of cocaine. Significant antibiotic ingestion was denied. At laparotomy, an edematous cecum and ascending colon were found, the cut surface of which revealed diffuse superficial ulcerations and yellowish fibrinous material. Microscopic examination demonstrated findings consistent with pseudomembranous colitis with an ischemic component. A mechanism in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1990
1990
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…In addition, there were 45 case reports among the included articles. 2 - 4 , 8 - 49 In addition to case reports, there were case series. 1 , 50 - 56 In the final step, manuscripts where the route of cocaine consumption was missing were excluded.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, there were 45 case reports among the included articles. 2 - 4 , 8 - 49 In addition to case reports, there were case series. 1 , 50 - 56 In the final step, manuscripts where the route of cocaine consumption was missing were excluded.…”
Section: Resultsmentioning
confidence: 99%
“…A retrospective study of 70 hospitalized patients found a significant difference in the white blood cell (WBC) counts of C. difficile-positive and C. difficile-negative patients (15,800/mm 3 vs. 7700/mm 3 ), demonstrating the utility of a frequently obtained lab marker in initial suspicion and subsequent diagnosis of CDI. 15,16 Newer advances in the diagnosis of CDI include nucleic acid amplification tests (NAAT) such as polymerase chain reaction (PCR), and stool testing for glutamate dehydrogenase (GDH). Figure 1 shows the histopathological findings in a 74 year male patient whose tissue sample was sent to our centre, who has history of diarrhea and use of antibiotics.…”
Section: Signs and Symptomsmentioning
confidence: 99%
“…Examples include alosetron, a selective serotonin antagonist used in the treatment of irritable bowel syndrome (IBS), cocaine, dextroamphetamine, gold, and glutaraldehyde, a disinfecting solution used to clean endoscopes. 4,66,98101 An isolated case report of paraquat (herbicide) toxicity causing PMC was published in 1981, but it is unclear what testing was pursued to make the diagnosis. It was presumed that vascular injury played a role in the initial colonic injury.…”
Section: Drugs and Toxinsmentioning
confidence: 99%